Larval Contracaecum sp (Nematoda : Anisakidae) in Hoplias malabaricus and Hoplerythrinus unitaeniatus (Osteichthyes : Erythrinidae) of economic importance in occidental marshlands of Maranhao, Brazil - Martins, M. L.; Onaka, E. M.; Fenerick, J. (Elsevier B.V., 2005)
This work describes the presence of Contracaecum sp. larvae (Nematoda: Anisakidae) found in food fish of economic importance captured in occidental marshlands in the State of Maranhao, Brazil. Hoplias malabaricus (Erythrinidae) and Hoplerythrinus unitaeniatus (Erythrinidae), commonly called traira and jeju, respectively, were examined. All H. malabaricus were infected with a mean intensity of 24.6 +/- 38.3 (1-137 parasites per host) while eighty percent of H. unitaeniatus showed a mean intensity of 10.4 +/- 9.2 (2-31) parasites. Nematodes were most similar to larvae of a type 2 described by Moravec, Kohn and Fernandes [Moravec, F., Kohn, A., Fernandes, B.M.M., 1993. Nematode parasites of fishes of the Parana River, Brazil. Part 2. Seuratoidea, Ascaridoidea, Habronematoidea and Acuarioidea. Folia Parasitol. 40, 115-134], but differed in having a longer intestinal caecum and greater caecum/ventricular appendix ratio. Larval measurements and a description of their Brazilian fish hosts are presented. (C) 2004 Elsevier B.V. All rights reserved.
Keywords: Nematoda; Contracaecum; Hoplias malabaricus; Hoplerythrinus unitaeniatus; description; Brazil